A Drosophila gene encoding a protein resembling the human beta-amyloid protein precursor. - Rosen, D R (1989)
We have isolated genomic and cDNA clones for a Drosophila gene resembling the human beta-amyloid precursor protein (APP). This gene produces a nervous system-enriched 6.5-kilobase transcript. Sequencing of cDNAs derived from the 6.5-kilobase transcript predicts an 886-amino acid polypeptide. This polypeptide contains a putative transmembrane domain and exhibits strong sequence similarity to cytoplasmic and extracellular regions of the human beta-amyloid precursor protein. There is a high probability that this Drosophila gene corresponds to the essential Drosophila locus vnd, a gene required for embryonic nervous system development.